2022
DOI: 10.31635/ccschem.021.202101160
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Ultrathin Carbon Nanoribbons from Metal–Organic Framework Nanorods for Oxygen Reduction and Zinc–Air Batteries

Abstract: Two-dimensional (2D) carbon nanostructures play a critical role for energy-related applications, while developing facile and efficient strategies to synthesize this kind of nanostructures is extremely rare.Herein, ultrathin carbon nanoribbons (CNRibs), with a thickness of 2-6 nanometers and length of hundred nanometers, have been strategically fabricated via a one-step pyrolysis of one-dimensional (1D) metalorganic framework nanorods (MOF NRods). Manipulating the diameters of MOF NRods will result in the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…But these catalysts exhibited efficient ORR performance in Zn-air cells beyond that of Pt/C catalysts. In particular, by calculating the partial density of states (PDOS) of each model (Figure 6g), it was found that the Pd-doped nanoribbons (Pd@GNRs) had the best ORR performance among these prepared samples, showing good stability for the RHE (reversible hydrogen electrode) with an onset potential of 0.94 V, high diffusion-limited current density of 5.87 mA/cm 2 , and a current retention of 95.4 % after 10 h. Similarly, Zou et al [93] synthesized FeÀ N-doped graphene nanoribbons (FeÀ NÀ GNRs) by a similar synthetic method and showed good ORR performance in both alkaline and acidic electrolytes with half-wave potentials of 0.89 and 0.74 V, respectively. It had also been found that the efficiency of FeÀ N x active center formation was highly dependent on the position of the N atom in the NÀ GNR precursor backbone, which allowed the formation of an N 2 center coordinated with the iron ion at the edge of the GNR (Figure 6i).…”
Section: Nanobeltssupporting
confidence: 52%
“…But these catalysts exhibited efficient ORR performance in Zn-air cells beyond that of Pt/C catalysts. In particular, by calculating the partial density of states (PDOS) of each model (Figure 6g), it was found that the Pd-doped nanoribbons (Pd@GNRs) had the best ORR performance among these prepared samples, showing good stability for the RHE (reversible hydrogen electrode) with an onset potential of 0.94 V, high diffusion-limited current density of 5.87 mA/cm 2 , and a current retention of 95.4 % after 10 h. Similarly, Zou et al [93] synthesized FeÀ N-doped graphene nanoribbons (FeÀ NÀ GNRs) by a similar synthetic method and showed good ORR performance in both alkaline and acidic electrolytes with half-wave potentials of 0.89 and 0.74 V, respectively. It had also been found that the efficiency of FeÀ N x active center formation was highly dependent on the position of the N atom in the NÀ GNR precursor backbone, which allowed the formation of an N 2 center coordinated with the iron ion at the edge of the GNR (Figure 6i).…”
Section: Nanobeltssupporting
confidence: 52%
“…[ 20 ] 1D structure such as nanorods and nanowires has the advantages of easy access to active sites and low contact resistance. [ 21 ] However, the morphology of PBAs is mainly cubic and thus the active site exposure is insufficient, resulting in the unsatisfied catalytic performance. How to regulate the relative growth rate of different crystal facets to controlled synthesize 1D PBAs is still a big challenge.…”
Section: Introductionmentioning
confidence: 99%
“…28 Similarly, Lianli et al synthesized Fe-N/ CNRib and studied the metal active sites immobilization during electrochemical performance. 29 Han et al investigated ORR catalytic activity of the UF Co-N-C electrocatalyst. 30 A promising way to increase the catalytic activity of M-N-C type materials is to introduce adjacent isolated metal centres which optimize the electronic structure of metal active sites and accelerate the ORR kinetics.…”
Section: Introductionmentioning
confidence: 99%